Analisis Kelayakan Ekonomi Pertanian Perkotaan (Urban Farming) Pada Kelompok Tani Yurga Farm Di Kota Surabaya - Avivah, Elmira Dhiva; Soedarto, Teguh; Santoso, Wahyu (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Surabaya City is one of the most densely populated cities in East Java, causing various social problems such as poverty, limited residential land, and lack of employment. To overcome these problems, the Surabaya City Agriculture Office developed an urban farming program as a form of community empowerment as well as an effort to strengthen food security. One of the farmer groups actively developing urban farming is Yurga Farm, which cultivates various types of horticultural vegetables on narrow but productive urban land. This study aims to analyze the economic feasibility of Yurga Farm's farming group. The data obtained in this study are primary data conducted by in-depth interviews regarding production costs, revenue, and income. The commodities cultivated include pakcoy, romen, siomak, lettuce, kale, samhong, caisim, and kale. The analysis showed that all commodities have an R/C Ratio value >1, the unit BEP is lower than production, and the price BEP is below the selling price. This indicates that the farming business is feasible, profitable, and has the potential to be developed sustainably